Thermal and structural properties of commercial dental resins light-cured with blue emitting diodes (LEDs) - Rojas, Seila Silva; Frigo, Geraldo José Mangerona; Bernardi, Maria Ines Basso; Rastelli, Alessandra Nara de Souza [UNESP]; Hernandes, Antonio Carlos; Bagnato, Vanderlei Salvador (Springer Nature, 2010)
We have investigated the thermal and structural properties of different commercial dental resins: FiltekTM Z-350, Grandio®, Tetric Ceram®, and TPH Spectrum®. The purpose of the present study was to evaluate quantitatively the photo-polymerization behavior and the effect of filler contents on the kinetic cures of the dental resins by using Differential Scanning Calorimetry (DSC) and Fourier Transform Infrared Spectroscopy (FT-IR) techniques. We have successfully obtained the low and high glass transition T g values of the dental composite resins from DSC curves. It was also observed a good agreement between the both T g values, activation energies from thermal degradation, and the degree of conversion obtained for all samples. The results have shown that Tetric Ceram® dental resin presented the higher T g values, activation energy of 215 ± 6 KJ mol−1, and the higher degree of conversion (63%) when compared to the other resins studied herein.
Keywords: Degradation; Dental resins; DSC; FT-IR; Thermal analysis